Fulfillment of Nutrition with Monitoring Children's Growth and Development in Efforts to Prevent Stunting in Early Age Children (JOYCED: Journal of Early Childhood Education, 2025)
Nutrition is an important factor in supporting the growth and development of early childhood. Good health will help optimize children's growth and development. This research aims to determine nutritional requirements and monitor children's growth and development at Darussalam Kindergarten, Yogyakarta. The method used in this research is descriptive qualitative. The sources of information in this research are teachers, school principals and children. Data collection techniques include observation, interviews and documentation. Data analysis techniques by reducing, presenting and drawing conclusions. The research results obtained show that Darussalam Kindergarten Yogyakarta has implemented various efforts to prevent stunting through a program to fulfill nutritional needs and monitor child growth and development. The program includes daily, monthly, and annual nutritional activities, as well as monitoring of Early Detection of Growth and Development (DDTK) carried out together with parents and the Health Center. In addition, health interventions such as deworming, vitamins, immunizations, and periodic weight and height measurements are also provided. The program has proven effective in preventing stunting. through programs that are implemented in a structured manner and involve various parties, especially parents and health workers, showing a holistic approach and potentially effective in preventing stunting. The active involvement of parents strengthens the continuity of monitoring child nutrition both at school and at home. The collaborative model implemented by Darussalam Kindergarten can be used as a reference for other early childhood education institutions in efforts to prevent stunting early and sustainably.
Keywords: Early Childhood; Growth and Development; Nutrition